Evaluation of intubation and intensive care use of the new Ambu® aScope™ 4 broncho and Ambu® aView™ compared to a customary flexible endoscope a multicentre prospective, non-interventional study. (April 2020) - Kriege, Marc; Dalberg, Jan; McGrath, Brendan A.; Shimabukuro-Vornhagen, Alexander; Billgren, Björn; Lund, Thomas Kromann; Thornberg, Klaus; Christophersen, Alice Vangerschov; Dunn, Mark J.G.
Abstract: Background: Flexible endoscopes have been well established for diagnostic and therapeutic interventions in critically ill patients. The purpose of this study was to compare the utility between the novel aScope 4 Broncho and the standard bronchoscope in a non-interventional study. Methods: In a prospective multicentre study, we evaluated the aScope 4 Broncho for different clinical indications involving an endoscopy procedure. We compared the acceptability of and preference for the novel Ambu® aScope™ 4 Broncho (Ambu® A/S, Ballerup, Denmark) with that of the customary flexible endoscope (reusable or single-use) normally used at each of the study centres. Results: A total of 176 aScope 4 Broncho-aided interventions were evaluated, and the primary finding of the study was that the aScope 4 Broncho was preferred over customary devices for both diagnostic/therapeutic bronchoscopy (58% preference, P  < 0.001), awake intubation with a flexible endoscope (65% preference, P  = 0.0026), and pooled data (59%, P  < 0.001). Conclusion: Possible reasons for the higher acceptability of and preference for the aScope 4 Broncho are the manoeuvrability of the scope and the optimised visualisation during tracheal intubation or of the bronchial system. Because of these benefits, any encountered risks may be reduced in patients undergoing bronchoscopic procedures, including in critically ill and presurgical/medical patients. Clinicaltrials.gov: NCT03294213. Registered: September 26, 2017. Highlights: Flexible endoscopy is a common diagnostic and essential therapeutic technique in critical care patients or used for difficult airway. In this multicentre study we investigated the novel aScope 4 Broncho single-use video-endoscope in 176 patients, undergoing awake video-optical intubation or bronchoscopy. The aim of the study was the comparison of the preference of each intervention, based on the physician's memory of their standard endoscope. The primary finding of the study was that the aScope 4 Broncho was preferred over standard methods for both bronchoscopy and intubation. The improved technical features (e.g. image quality, bending angle with 180° ante-/reflection) of the aScope 4 Broncho may have led to the results.